Implementing "dama" game using parallel search - Huilar, Arvel L. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
"Dama" is a common traditional board game of Filipinos. In this study, the game was developed based on its usability and application of parallel search algorithm for faster response time. These include the dynamics of "dama" game, alpha-beta pruning algorithm, sequential and parallel PVSplit algortihms and graphical user interface. In order for the game to have intelligence, improved search algorithms such as the use of the PVSplit algorithm to exploit parallelism was employed. This was shown to speed up the efficiency of the implemented algorithm run on high performance computer with a speedup of 3. However, the use of the same algorithm an on a cluster of computers showed a lower performance. This algorithm performed better than the alpha-beta algorithm especially in finding better intelligent moves. This study has also shown that the playable "dama" game designed with a graphical user interface familiar to "dama" players has a perceived usability using System Usability Scale of 81.3 SUS score, high enough to be recommended for use. This was favorably supported by positive feedback from the user qualified asclass B by the experts.